Patterns of use of drugs in hypertension in geriatric patients in the department of medicine at tertiary care hospital of Nepal. - Raut, Binod; Khadka, Anjan (Birat Journal of Health Sciences, 2020)
Introduction: In Nepal, the prevalence of hypertensive in elderly population is 41.7% aged 65 years or more. Hypertension increases with age leading to arterial stiffness and endothelial dysfunction. The prevalence of hypertension is 20% of urban populations. Blood pressure control with the use of antihypertensive drugs reduces cardiovascular complications in geriatric patients. Objectives: The objective of our study is to know the various patterns of drugs used in geriatrics hypertensive patient along with their co-morbidities and to know the most commonly used antihypertensive drug in geriatric patient. Methodology: It was a hospital based cross sectional study involving 130 patients based on non-probability sampling. The study involved the hypertensive elderly patients of age > 65 years prescribed with antihypertensive drugs. Data were collected from patients attending outpatient department of medicine . Medical and nursing records were analyzed for patient’s characteristics (e.g. age, gender), systolic and diastolic BP readings, number of drugs, monotherapy, combination therapy, co morbidities. Data were analysed by using SPSS version 20. Results: The total 130 geriatric patients under treatment with antihypertensive drugs were included, in which 55.38% were male and 44.62% were female. The total numbers of antihypertensive drugs prescribed were 212 either as monotherapy or as a component of a combination therapy. The average number of drugs prescribed per patient was found to be 1.66. Among these drugs 56.92% were prescribed as monotherapy,26.92% were prescribed as two drugs combination therapy,12.30% were prescribed as three drugs combination and 3.84% were prescribed as four drugs combination therapy. calcium channel blockers (amlodipine )was the most commonly prescribed antihypertensive. Conclusion: The study showed male patient were more predominant hypertensive compare to female. calcium channel blockers group of drugs in which amlodipine was the most commonly prescribed antihypertensive drug and more than half of the patients were in monotherapy.